Orpaillage filonien et facteurs d’ancrage territorial au Burkina Faso : le cas de la commune de Kampti - Edith Sawadogo; Kouka Sawadogo (EchoGéo)
Gold panning is an ancient practice of the populations of southwest Burkina Faso but the contemporary resumption of this activity by "exogenous" artisan miners in the early 2000s, was not without difficulty. However, artisanal miners were able to integrate into these former territories where gold panning was a female activity, across the southwest region of the country. The objective of this research is to analyse the actions of "exogenous" miners towards local populations that have enabled their territorial integration. The methodological approach is qualitative, based on group and individual interviews with 64 people in the mining sites and villages of Fofora and Dindoura in the commune of Kampti. This collection was supplemented by observations in the field. It appears that "exogenous" artisan miners, in addition to renting spaces for their activities, involve local populations in shaft mining, by associating them or hiring them. In addition, they carry out projects in favor of local residents, similar to the Corporate Social Responsibility (CSR) observed in the formal and industrial mining sector. These actions contribute to their anchoring and legitimization in village territories previously hostile to gold mining.